incidencia y medidas de control de la roya del café en la producción cafetalera del ecuador - Castillo Villavicencio, Nestor Andres (Machala : Universidad Técnica de Machala, 2022)
In this study, an approach to coffee production in Ecuador was made. However, as a country with a coffee tradition, coffee production has suffered a deep recession since the 1990s and has yet not recovered. The methodology of this study is documentary. Among all the conclusions, the most remarkable to be mentioned is that the very low production experienced by coffee is related to Hemileia vastatrix coffee rust, which has caused a decrease in production for various reasons. Many farmers do not know how to control this disease, so they do not have the proper training, they do not know the stages of coffee rust, they do not know when and how to control it. Being one of the most devastating diseases, there is much discussion about the management of rust or the form of control that can be used, and most coffee growers have focused on the use of fungicides and cultural practices, biological one is one of the most promising measures, the use of endophytic microorganisms. But when the disease is very advanced, the use of systemic products helps the protection of the plant to be more lasting and less harmful.
En este estudio se realizó un acercamiento a la producción de café en el Ecuador. Sin embargo, como país de tradición cafetalera, la producción cafetalera ha sufrido una recesión vertiginosa desde la década de 1990 y aún no se recupera. La metodología de este estudio es documental. Entre todas las conclusiones, la más importante a ser mencionada es que la bajísima producción que experimenta el café tiene relación con la roya del café (Hemileia vastatrix), lo que ha provocado una disminución de la producción por diversos motivos. Muchos agricultores no saben cómo controlar esta enfermedad, por lo que no tienen la capacitación adecuada, no conocen las etapas de la roya del café, no saben cuándo y cómo controlarla. Al ser una de las enfermedades más devastadoras existe mucha discusión sobre el manejo de la roya o la forma de control que se pueda emplear, y la mayoría de los caficultores se han centrado en el uso de fungicidas y las prácticas culturales, siendo las biológicas una de las medidas más prometedora es el uso de microorganismos endófitos. Pero cuando la enfermedad está muy avanzada el uso de productos sistémicos ayuda a que la protección de la planta sea más duradera y menos dañina.
Keywords: CAFÉ; ROYA DEL CAFÉ; ENFERMEDAD; HEMILEIA VASTATRIX